Sealant, fireproof wave-absorbing material and application thereof

By using sealants prepared from aerogels, polyacrylates and other materials, the problem of insufficient flame retardant performance of wave absorbing materials under high temperature and fire conditions is solved, and the material is excellent wave absorbing and flame retardant performance is achieved, and the material has good mechanical and waterproof performance is good.

CN119799212AActive Publication Date: 2025-04-11HAINAN UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510023938.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The existing wave-absorbing materials have insufficient flame retardant performance under high temperature and fire conditions, making it difficult to meet the increasingly stringent flame retardant requirements. At the same time, the addition of flame retardant may affect the electromagnetic performance.

Method used

The sealant material is prepared by mixing and curing aerogel, polyacrylate, titanium dioxide, calcium carbonate, gas-phase nanosilica and water. The aerogel is composed of graphene oxide, carbon nanotubes, and ammonium polyphosphate wrapped in carbon black. Through the combined action of these components, the material is achieved with excellent wave absorption and flame retardant properties.

Benefits of technology

This sealant material not only has excellent wave absorption and flame retardant properties, but also has good mechanical properties and waterproof properties. It can effectively prevent the spread of flames under high temperature and fire conditions and reduce fire risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005232191670000071
    Figure BDA0005232191670000071
  • Figure BDA0005232191670000081
    Figure BDA0005232191670000081
  • Figure HDA0005232191680000011
    Figure HDA0005232191680000011
Patent Text Reader

Abstract

The invention discloses a sealant, a fireproof wave-absorbing material and application of the fireproof wave-absorbing material, and belongs to the technical field of wave-absorbing flame retardance. The sealant is prepared by mixing and curing aerogel, polyacrylate, titanium dioxide, calcium carbonate, gas-phase nano silicon dioxide and water, wherein the aerogel is prepared by mixing graphene oxide, carbon nanotubes, carbon black coated ammonium polyphosphate and water, reacting and drying. The sealant has excellent flame-retardant and wave-absorbing properties and good waterproof performance through the combined action of the aerogel and other raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of wave-absorbing and flame-retardant technology, and in particular to a sealant, a fireproof wave-absorbing material and applications thereof. Background Art

[0002] In the field of construction, fire safety has always been a concern. Fireproof sealants are essential for fire prevention. They are mainly used in the joints of building curtain walls to ensure effective fire prevention at the gaps.

[0003] In the field of communications, absorbing materials, as a special functional material, are widely used in radar stealth, electromagnetic protection, wireless communications and other fields. However, in some application scenarios, absorbing materials may face extreme conditions such as high temperature and fire, so flame retardancy has become an important indicator of absorbing materials. The importance of flame retardancy to absorbing materials is mainly reflected in the following aspects: First, flame retardancy can improve the safety of absorbing materials and reduce the risk of fire; second, flame retardancy helps to protect the safety of equipment and personnel and avoid losses caused by fire; finally, flame retardancy can improve the reliability and stability of absorbing materials and extend their service life. Therefore, flame retardancy has an important impact on the research and development and application of absorbing materials.

[0004] At present, the flame retardant properties of absorbing materials can be achieved through the following methods: (1) Adding flame retardants. Flame retardants can decompose under high temperature conditions to produce non-flammable gases, thereby preventing the spread of flames. (2) Changing the composition of the material. By adjusting the composition of the absorbing material, it can have better thermal stability and flame retardant properties at high temperatures. However, achieving flame retardant properties of absorbing materials also faces some challenges. For example, the addition of flame retardants may affect the electromagnetic properties of the absorbing material. New flame retardant absorbing materials need to be continuously improved to meet increasingly stringent flame retardant requirements.

[0005] The fire safety issue of prefabricated fireproof and electromagnetic radiation proof buildings has always attracted much attention. Therefore, it is of great significance to study a multifunctional sealant material that has excellent microwave absorption and flame retardant properties and can be used for fire protection of building curtain wall joints. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a sealant, a fireproof and wave-absorbing material and their application. The sealant has excellent wave-absorbing and flame-retardant properties, as well as good mechanical properties and waterproof properties.

[0007] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] The present invention provides a sealant, which is prepared by mixing and curing aerogel, polyacrylate, titanium dioxide, calcium carbonate, gas-phase nano-silicon dioxide and water;

[0009] The aerogel is prepared by mixing graphene oxide, carbon nanotubes, ammonium polyphosphate wrapped by carbon black and water, and drying.

[0010] The carbon black-wrapped ammonium polyphosphate is homemade.

[0011] The sealant of the present invention can effectively prevent fire and absorb waves through the combined action of the aerogel, polyacrylate and other raw materials.

[0012] Preferably, in the present invention, the mass ratio of the graphene oxide, carbon nanotubes and carbon black-wrapped ammonium polyphosphate is 4:1:(1-5): more preferably 4:1:5.

[0013] Preferably, the aerogel accounts for 5wt% to 30wt% of the mass of the sealant; more preferably, the aerogel accounts for 5wt% to 15wt% of the mass of the sealant; in some specific embodiments of the present invention, it is preferably 7.5wt%.

[0014] Preferably, the calcium carbonate accounts for 20 wt% to 30 wt% of the mass of the sealant, and in some specific embodiments of the present invention, preferably 27.5 wt%.

[0015] Preferably, the gas-phase nano-silicon dioxide accounts for 1 wt % of the mass of the sealant.

[0016] The mass ratio of the titanium dioxide to water is 1:(1.5-3); more preferably 1:2.

[0017] Preferably, the mixed and solidified raw materials also include a defoamer and a dispersant.

[0018] Preferably, the drying is selected from freeze drying.

[0019] The freeze drying preferably uses liquid nitrogen freezing.

[0020] The mixing reaction is preferably carried out under ultrasound.

[0021] Preferably, the curing temperature is 60°C to 80°C; in some specific embodiments of the present invention, it is 60°C.

[0022] Preferably, the curing time is 12 hours to 24 hours, and in some specific embodiments of the present invention, it is 12 hours.

[0023] The present invention also provides a fireproof wave-absorbing material, comprising the above-mentioned sealant.

[0024] Preferably, the reflectivity of the fireproof wave-absorbing material is -45 to -10 dB;

[0025] Preferably, the limiting oxygen index of the fireproof and wave-absorbing material is 22.6 to 27.6 vol%;

[0026] The L94 test of the fireproof and absorbing material is V-0 or V-1 grade;

[0027] Preferably, the hydrophobicity of the fireproof and wave-absorbing material is 0.08% to 0.17%.

[0028] The present invention also provides the use of the fireproof and electromagnetic radiation absorbing material in assembled fireproof and electromagnetic radiation proof buildings.

[0029] Compared with the prior art, the sealant provided by the present invention is prepared by mixing and curing aerogel, polyacrylate, titanium dioxide, calcium carbonate, fumed nano-silicon dioxide and water: the aerogel is prepared by mixing graphene oxide, carbon nanotubes, carbon black-wrapped ammonium polyphosphate and water, and drying. The sealant has excellent flame retardant and wave absorbing properties and good waterproof properties through the combined action of aerogel and other raw materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a diagram showing the wave absorption performance of the sealant prepared in Example 1;

[0031] Figure 2 This is the appearance of the sealant prepared in Example 1 after burning;

[0032] Figure 3 The mechanical properties of the multifunctional fireproof sealants prepared in Examples 1 to 5 and Comparative Example 1 are shown in FIG.

[0033] Figure 4 This is a graph showing the water absorption results of the multifunctional fireproof sealants prepared in Examples 1 to 5 and Comparative Example 1. DETAILED DESCRIPTION

[0034] In order to further illustrate the present invention, the sealant, fireproof and wave-absorbing material and their applications provided by the present invention are described in detail below in conjunction with embodiments.

[0035] The following homemade method of carbon black-wrapped ammonium polyphosphate comprises the following steps:

[0036] Under N2 atmosphere, 70g of ammonium polyphosphate (APP), 5g of silane coupling agent KH792 and 200mL of anhydrous ethanol were added to a round-bottom flask and stirred at room temperature for 1h to obtain solution A. Then, nano-CB was dispersed in 100mL of ethanol and 100mL of deionized water by ultrasonic treatment for 30min, which was solution B. Solution A and solution B were ultrasonically mixed for 30min to obtain carbon black-encapsulated ammonium polyphosphate. Subsequently, the temperature was raised to 80°C for 4h. Finally, the solvent was removed with deionized water and ethanol and vacuum dried at 60°C for 12h.

[0037] The following aerogel homemade method includes the following steps:

[0038] Graphene oxide, carbon nanotubes, ammonium polyphosphate wrapped by carbon black and water are mixed and reacted in proportion. The mechanism is as follows: in the sol, graphene oxide, carbon nanotubes, ammonium polyphosphate wrapped by carbon black form a network structure through mutual connection and aggregation.

[0039] The carbon nanotubes described below contain hydroxyl groups.

[0040] About the reaction between graphene oxide, carbon nanotubes and carbon black-wrapped ammonium polyphosphate.

[0041] Example 1

[0042] A preparation process of a multifunctional waterproof sealant based on aerogel comprises the following steps:

[0043] S1. Preparation of aerogel: Graphene oxide, carbon nanotubes, carbon black-wrapped ammonium polyphosphate and water were mixed evenly in a 100 mL beaker according to a certain mass ratio (i.e., corresponding to 40 mg: 10 mg: 50 mg, water 15 mL), and ultrasonicated for 1 hour;

[0044] S2, freeze drying: freeze S1 in a homemade mold with liquid nitrogen, observe the dispersion liquid in a frozen state, and put it into a freeze dryer for drying;

[0045] S3, preparation of functional sealant: add appropriate amount of water to dissolve titanium dioxide, stir for ten minutes, then add calcium carbonate, fumed nano-silica and aerogel for dispersion (wherein, aerogel is 5wt% of the mass of the functional sealant, calcium carbonate is 30wt% of the mass of the functional sealant, and fumed nano-silica is 1wt% of the mass of the functional sealant), the rotation speed is 500-600r / min; at the same time, add defoamer and dispersant, add 60wt% polyacrylate after ten minutes, set the power to 60%, stir at high speed (speed is 2000-3000r / min), disperse the mixture to a fineness of less than 10μm, and then place the mixture in a vacuum to eliminate bubbles;

[0046] S4, curing functional sealant: place S3 in a drying oven for curing at a temperature of 60°C for 12 hours;

[0047] S5. The performance test of the functional sealant after curing is shown in Table 1.

[0048] Figure 1 This is a graph of the wave absorption performance of the sealant prepared in Example 1. The results show that at a wave frequency of 2-18 and a thickness of 2 mm, the reflectivity reaches -10 dB.

[0049] Example 2

[0050] A preparation process of a multifunctional waterproof sealant based on aerogel comprises the following steps:

[0051] S1. Preparation of aerogel: Graphene oxide, carbon nanotubes, carbon black-wrapped ammonium polyphosphate and water were mixed evenly in a 100 mL beaker according to a certain mass ratio (i.e., 40 mg: 10 mg: 50 mg, 15 mL of water), and ultrasonicated for 1 hour;

[0052] S2, freeze drying: freeze S1 in a homemade mold with liquid nitrogen, observe the dispersion liquid in a frozen state, and put it into a freeze dryer for drying;

[0053] S3, preparation of functional sealant: add appropriate amount of water to dissolve titanium dioxide, stir for ten minutes, then add calcium carbonate, fumed nano-silica and aerogel for dispersion (wherein, aerogel is 7.5wt% of the mass of the functional sealant, calcium carbonate is 27.5wt% of the mass of the functional sealant, and fumed nano-silica is 1wt% of the mass of the functional sealant), the rotation speed is 500-600r / min; at the same time, add defoamer and dispersant, add 60wt% polyacrylate after ten minutes, set the power to 60%, stir at high speed (speed is 2000-3000r / min), disperse the mixture to a fineness of less than 10μm, and then place the mixture in a vacuum to eliminate bubbles;

[0054] S4, curing functional sealant: place S3 in a drying oven for curing at a temperature of 60°C for 12 hours;

[0055] S5. The performance test of the functional sealant after curing is shown in Table 1.

[0056] Example 3

[0057] A preparation process of a multifunctional waterproof sealant based on aerogel comprises the following steps:

[0058] S1. Preparation of aerogel: Graphene oxide, carbon nanotubes, carbon black-wrapped ammonium polyphosphate and water were mixed evenly in a 100 mL beaker according to a certain mass ratio (i.e., corresponding to 40 mg: 10 mg: 50 mg, water 15 mL), and ultrasonicated for 1 hour;

[0059] S2, freeze drying: freeze S1 in a homemade mold with liquid nitrogen, observe the dispersion liquid in a frozen state, and put it into a freeze dryer for drying;

[0060] S3, functional sealant preparation: add an appropriate amount of water to dissolve titanium dioxide, stir for ten minutes, then add calcium carbonate, fumed nano-silica and aerogel for dispersion (wherein, aerogel is 10wt% of the mass of the functional sealant, calcium carbonate is 25wt% of the mass of the functional sealant, and fumed nano-silica is 1wt% of the mass of the functional sealant), the rotation speed is 500-600r / min; at the same time, add defoamer and dispersant, add 60wt% polyacrylate after ten minutes, set the power to 60%, stir at high speed (speed is 2000-3000r / min), disperse the mixture to a fineness of less than 10μm, and then place the mixture in a vacuum to eliminate bubbles;

[0061] S4, curing functional sealant: place S3 in a drying oven for curing at a temperature of 60°C for 12 hours;

[0062] S5. The performance test of the functional sealant after curing is shown in Table 1.

[0063] Example 4

[0064] A preparation process of a multifunctional waterproof sealant based on aerogel comprises the following steps:

[0065] S1. Preparation of aerogel: Graphene oxide, carbon nanotubes, carbon black-wrapped ammonium polyphosphate and water were mixed evenly in a 100 mL beaker according to a certain mass ratio (40 mg: 10 mg: 50 mg, water 15 mL), and ultrasonicated for 1 hour;

[0066] S2, freeze drying: freeze S1 in a homemade mold with liquid nitrogen, observe the dispersion liquid in a frozen state, and put it into a freeze dryer for drying;

[0067] S3, preparation of functional sealant: add appropriate amount of water to dissolve titanium dioxide, stir for ten minutes, then add calcium carbonate, fumed nano-silica and aerogel for dispersion (wherein, aerogel is 12.5wt% of the mass of the functional sealant, calcium carbonate is 22.5wt% of the mass of the functional sealant, and fumed nano-silica is 1wt% of the mass of the functional sealant), the rotation speed is 500-600r / min; at the same time, add defoamer and dispersant, add 60wt% polyacrylate after ten minutes, set the power to 60%, stir at high speed (speed is 2000-3000r / min), disperse the mixture to a fineness of less than 10μm, and then place the mixture in a vacuum to eliminate bubbles;

[0068] S4, curing functional sealant: place S3 in a drying oven for curing at a temperature of 60°C for 12 hours;

[0069] S5. The performance test of the functional sealant after curing is shown in Table 1.

[0070] Example 5

[0071] A preparation process of a multifunctional waterproof sealant based on aerogel comprises the following steps:

[0072] S1. Preparation of aerogel: Graphene oxide, carbon nanotubes, carbon black-wrapped ammonium polyphosphate and water were mixed evenly in a 100 mL beaker according to a certain mass ratio (i.e., corresponding to 40 mg: 10 mg: 50 mg, water 15 mL), and ultrasonicated for 1 hour;

[0073] S2, freeze drying: freeze S1 in a homemade mold with liquid nitrogen, observe the dispersion liquid in a frozen state, and put it into a freeze dryer for drying;

[0074] S3, functional sealant preparation: add an appropriate amount of water to dissolve titanium dioxide, stir for ten minutes, then add calcium carbonate, fumed nano-silica and aerogel for dispersion (wherein, aerogel is 15wt% of the mass of the functional sealant, calcium carbonate is 20wt% of the mass of the functional sealant, and fumed nano-silica is 1wt% of the mass of the functional sealant), the rotation speed is 500-600r / min; at the same time, add defoamer and dispersant, add 60wt% polyacrylate after ten minutes, set the power to 60%, stir at high speed (speed is 2000-3000r / min), disperse the mixture to a fineness of less than 10μm, and then place the mixture in a vacuum to eliminate bubbles;

[0075] S4, curing functional sealant: place S3 in a drying oven for curing at a temperature of 60°C for 12 hours;

[0076] S5. The performance test of the functional sealant after curing is shown in Table 1.

[0077] Comparative Example 1

[0078] The difference from Example 1 is that in Example 1, the aerogel prepared by S1 is not added.

[0079] 1. Test verification

[0080] The aerogel-based multifunctional waterproof sealants prepared in the above Examples 1-5 and Comparative Example 1 were subjected to combustion performance and tensile performance tests.

[0081] The combustion performance is tested in accordance with the horizontal and vertical methods of GB / T 2408-2008 Plastic Combustion Performance (IEC60695-11-10:1999, IDT); the tensile performance test is tested in accordance with GB / T13477.8-2002 Test Methods for Building Sealing Materials Part 8: Determination of Tensile Adhesion (ISO8339:1984, MOD).

[0082] Among them, the wave absorption (reflectivity) standard is: the composite material and paraffin are evenly mixed at a mass ratio of 20wt%, and pressed into a ring sample to be tested, in which the inner diameter, outer diameter and thickness are 3.04, 7.00 and 2.00mm respectively. The electromagnetic parameters are obtained by a vector network analyzer using a coaxial method in the frequency range of 2.0-18.0GHz. The transmission line theory is used to calculate the reflection loss (RL) value of absorbers of different thicknesses at their corresponding frequencies.

[0083] The water absorption rate is based on the ASTM D570 implementation standard. At room temperature, a Biolin Scientific contact angle meter is used to measure the static contact angle of the liquid on the surface of the adhesive layer. The test drop volume is 5 μL, and the liquid used in the test is deionized water.

[0084] Table 1 Performance test results

[0085]

[0086]

[0087] From the above results, it can be seen that among the sealants described in the present invention, Example 2 has the best reflection loss, reaching -45dB. At the same time, the flame retardant and waterproof properties are also continuously improved. When the amount of aerogel is small (Example 1), compared with Comparative Example 1, the wave absorbing performance, flame retardant performance, mechanical properties and waterproof performance of Example 1 are significantly better than those of Comparative Example 1. And the wave absorbing performance of Example 2 described in the present invention reaches the best.

[0088] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A sealant, characterized in that: It is prepared by mixing and solidifying aerogel, polyacrylate, titanium dioxide, calcium carbonate, fumed nano-silicon dioxide and water; The aerogel is prepared by mixing graphene oxide, carbon nanotubes, ammonium polyphosphate wrapped by carbon black and water, and drying.

2. The sealant according to claim 1, characterized in that: The mass ratio of the graphene oxide, the carbon nanotubes and the ammonium polyphosphate wrapped by carbon black is 4:1:(1-5).

3. The sealant according to claim 1, characterized in that: The aerogel accounts for 5wt% to 30wt% of the mass of the sealant.

4. The sealant according to claim 1, characterized in that: The calcium carbonate is 20wt% to 30wt% of the mass of the sealant; The fumed nano-silicon dioxide is 1wt% of the mass of the sealant; The mass ratio of the titanium dioxide to water is 1:(1.5-3).

5. The sealant according to claim 1, characterized in that: The mixed and solidified raw materials also include a defoamer and a dispersant.

6. The sealant according to claim 1, characterized in that: The drying is selected from freeze drying.

7. The sealant according to claim 1, characterized in that: The curing temperature is 60°C to 80°C; The curing time is 12h to 24h.

8. A fireproof wave absorbing material, characterized in that: The invention comprises the sealant as claimed in any one of claims 1 to 7.

9. The fireproof wave absorbing material according to claim 8, characterized in that: The reflectivity of the fireproof wave-absorbing material is -45 to -10 dB; The limiting oxygen index of the fireproof and wave-absorbing material is 22.6 to 27.6 vol%; The UL94 test of the fireproof and wave-absorbing material is V-0 or V-1 grade; The hydrophobicity of the fireproof wave-absorbing material is 0.08% to 0.17%.

10. Use of the fireproof and wave-absorbing material according to claim 8 or 9 in assembled fireproof and electromagnetic radiation proof buildings.

Citation Information

Patent Citations

  • Sealant

    CN103805086A

  • High-conductivity carbon nanotube / graphene aerogel / polystyrene composite and preparation method thereof

    CN107286491A

  • Expandable graphite modified flame retardant polyurethane sealant and preparation method thereof

    CN108359403A

  • High-temperature-resistant conductive wave-absorbing sealing material

    CN111875964A

  • Silane modified polyacrylate sealant and preparation method thereof

    CN112538326A